Optimal clarification of emulsified oily wastewater using a surfactant/chitosan biopolymer - Perez Calderon, John Freddy (2018)
The presence of emulsified oils in wastewater from the petroleum and petrochemical industry causes a significant environmental concern. The effect of chitosan (CH) and sodium dodecyl sulfate (SDS) doses on the destabilization of emulsified wastewater was analyzed based on key parameters such as: residual turbidity (% RT), relative length of the clarified zone (CL), chemical oxygen demand (% COD) and zeta potential (ZP). A response surface methodology and central composite design were applied for optimizating the influence of CH and SDS doses, on the performance of the demulsification process. A desirability test allowed to calculate the optimal doses of CH and SDS to produce: i) minimum values of%RT and ZP and ii) maximum values of CL and % COD removal. A novel kinetic model based on first order equations for both stages: coagulation/flocculation and settling of the flocs was proposed to describe clarification using measurements of static dispersion of light and back scattering profiles (BS). The proposed model is a useful tool for predicting clarification times and to analyze the governing mechanisms of the process. Coagulation/flocculation occurs in less than 3 h reaching very low turbidity values in the clarified zone (<11% RT). Additionally, the BS profiles after 3 h showed that at the optimal dosage of CH and SDS 70% of the total volume was clarified with a total hydrocarbon removal of 98.61%. This study demonstrates that CH constitutes a potent flocculating/coagulating agent in waste-water emulsified systems from petroleum industry.